Expectations for habitat-adapted symbiosis in a winter annual grass. (October 2017) - Griffith, David L.; Larkin, Beau; Kliskey, Andrew; Alessa, Lilian; Newcombe, George
Abstract: The habitat-adapted symbiosis hypothesis predicts that the most positive effects of symbiosis are expected in the most stressful sites for a plant host. Stress varies with site characteristics but also during the life cycle of a plant, with winter annuals experiencing the most stress after fall emergence. For Bromus tectorum, fecundity can vary tremendously from a few to thousands of seeds per plant. We used endophytic Sordaria fimicola to test the hypothesis in three sites in western Montana. We hypothesized that the effects of S. fimicola inoculation would be most positive in the most stressful site after fall application. As predicted, the most positive effects on growth and fecundity were observed in the most stressful site after fall application of S. fimicola . However, the effects of treatments varied within and between sites considerably, and are best understood as an example of context-dependency in plant-microbe interactions rather than habitat-adapted symbiosis.